The Effect of Aerobic Exercise on Renal Function and Metabolic Syndrome in Kidney Transplant Athletes - Homa Sheikhani shahin; Golnoosh Mehrabani; Rasoul Rezaei; Mohsen Karimi; Masoud Amini (Journal of Advanced Biomedical Sciences, 2017)
Background & Objectives: The relationship between metabolic disorders and renal functions in kidney transplant recipients has been reported. Considering the identification of many advantages of regular physical activities in maintaining health, for chronic kidney patients, the researchers tried to study the effect of aerobic activities on renal function and metabolic syndrome in kidney transplant athletes. Materials & Methods: Twenty female kidney transplant athletes were randomly selected and divided into two equal groups of experimental (mean of age =24.5±2.7 years, height=161±4.2 cm and weight= 57.9±1.8 kg) and control (mean of age =24.9±2.3 years, height=162±2.4 cm and weight= 59.5±4.02 kg). The experimental group carried out an exercise for eight weeks (three sessions per week). At the end of eighth week, the renal function was assessed based on glomerular filtration rate and metabolic syndrome indices. Paired-samples t-test was used to compare the data before and after physical exercise and independent-samples t-test was used to compare the two groups with the significance level of p< 0.05.